Education Leaders, Research Scholars, and Expert Practitioners: Feedback of Employers and Immediate Heads of Educational Management Graduates - Michael Aquino, John; Jobelle Culajara, Carla; Ancho, Inero; Arrieta, Gilbert; Barrameda, Caridad (ASEAN Journal of Education, 2023)
The institution under the present study desires to provide education leaders, research scholars, and innovative teachers with the values of truth, excellence, and service. The findings of the study strengthen the attributes of the graduates as education leaders. Based on the employer and immediate head feedback, graduates have possessed the capacity to provide directions of the institution, lead projects and committees, and provide accountability by demonstrating ethical, transformative, and equitable leadership. As research scholars, graduates have exhibited promising feedback, especially in an era when research is emphasized in informed decisionmaking and evidence-based practices, with a mean of 3.865. M.A. and Ph.D. graduates are equipped with the necessary skills needed to conceptualize, plan, and conduct academic inquiries anchored on practices and institutional agenda, with a mean of 3.841. M.A. and Ph.D. graduates are considered education leaders, with a mean of 3.84, who can link theory into practice, and actualize philosophical and theoretical underpinnings of the educational management program by highlighting intercultural competency, ethical leadership, and sensitivity and respect to various beliefs and ways of life.